Analysis of Factors Affecting The Sustainability of Using Online Loan Applications Using The Information System Success Model and Expectation Confirmation Model - Kevin Tito Hutahaean; Endang Sugiharti (Universitas Negeri Semarang, 2024)
The rapid digitization of financial services has spurred the growth of cashless lending systems, with online lending emerging as a prominent method for individuals and businesses to access funds. This trend is driven by the ease of loan application through online platforms and the challenges associated with traditional bank loans. However, online loans often come with higher interest rates compared to conventional banks, raising concerns about users' long-term engagement with these platforms. This study investigates the factors influencing the continuance intention of users in utilizing online loan applications. Employing a quantitative approach, the research integrates the Information System Success Model (ISSM) and the Expectation Confirmation Model (ECM) to examine 13 variables across 24 hypotheses. Data was collected via Google Forms, distributed through social media, targeting individuals aged 17 to 55 in Indonesia who had previously applied for online loans. After rigorous data screening, 227 valid responses were analyzed using SmartPLS. The findings revealed that out of the 13 variables, use, satisfaction, and debt attitudes significantly influence continuance intention, while other factors like perceived usefulness and impulsive buying were less impactful. Future studies should explore a broader respondent base and incorporate variables such as interest rates and urgency to provide a more comprehensive understanding of users' continued use of online loan applications.